A leitura e a escrita na primeira etapa da educação infantil: os discursos e as práticas pedagógicas - Souza, Lilian Silva de Lucas de [UNESP] (2014)
The purpose of this dissertation is to focus on teaching practices related to children's interaction with the literate world. Such practices were performed in early childhood education, which cater to children aged zero to three years old. During the research, we verified the conceptions of teaching and learning how to read and write, which play a dominant role in educators' practices and speeches. Initially, we present a brief history of this mode of education. Following, we focus on the most common epistemological conceptions in teaching, so we can later analyze the teaching practices and their implications in the process of learning to read and write. The research was carried out in the Municipality of Rio Claro, SP, Brazil. The municipal schools were chosen according to their classification into three large groups: big schools (12 classrooms); medium-sized schools (six classrooms) and small schools (four classrooms). After this classification, one school of each group was picked according to the Fisher-Yates Shuffle (1957), totaling 18.75% of day-care centers in the Municipality. Seventeen educators participated in the research: six teachers and 11 teaching assistants. Data was collected by observing classes and interviewing the educators. The observations were registered in a field log and audio recordings. The interviews were performed at times arranged with the participants, and they were also recorded and, then, totally transcribed. The collected and analyzed data showed that the reading and writing-related didactic approaches observed in the classroom are based on the conceptions of either the empiricist or aprioristic epistemology. Four out of the six participating teachers presented innovating activities in their practices. Both the assistants' and the teachers' speeches showed a mixture of conceptions, thus demonstrating a contradiction between their practice and ... (Complete abstract electronic access below)